Flouting Maxim Of Grice’s Cooperative Principle In An Exclusive Interview With Chris Martin Of Coldplay In Mata Najwa Talkshow - Sari, Ririn Novita; Rullyanti, Merry; Pradana, Ami (Literary Criticism, 2025)
The focus of this research was to analyse the extent of flouting maxim of Grice’s Cooperative principle done by Chris Martin, vocalist of the band Coldplay and analyse the types of flouting Grice’s Cooperative principle used by guests and their reasons, this interview hosted by NajwaShihab in the Mata Najwa program which is a highly interactive talk show entitled "Exclusive Interview with Chris Martin of Coldplay | Mata Najwa". The research uses a descriptive qualitative and quantitative method since the data is presented as words and numbers. The reason for choosing this talk show is because Chris Martin is an English native speaker, while NajwaSihab is an Indonesian native speaker, making it possible to compare how Grice's Cooperative principle is often flouted during interviews due to language and cultural differences. Inan exclusive interview as shown in this study, 11 utterances were found during the interview, including 4 utterances that flouting maxim quantity, 4 utterances that flouting maxim quality, 2 utterances that flouting maxim relevance and 1 utterance that flouting maxim manner. From the data of flouting maxim, that also found several reasons why Chris do the flouting maxim, these reasons areconfusing in giving answer, friendliness, respectful, confidentiality/hiding the truth and Showing empathy. And the most common reason for flouting maxim was found when Chris flouted maxim quantity and quality. As this was a formal interview, the flouting Grice’s Cooperative principle was done by politeness strategies. Despite the flouting Grice’s Cooperative principle, the conversation still runs well until the end. Keyword: Cooperative Principle, Flouting Maxim, Grecian Maxim, Mata Najwa.